2021
DOI: 10.3390/su131910659
|View full text |Cite
|
Sign up to set email alerts
|

Traditional Brick Making, Environmental and Socio-Economic Impacts: A Case Study of Vhembe District, South Africa

Abstract: The brick making industry, despite its contribution to environmental pollution, plays a major role in the economic growth of South Africa, with the traditional technology accounting for a significant proportion of the total clay brick production. The aim of this study is to undertake a comprehensive description of the production phases of the traditional brick making sector in Vhembe district and how this contributes to air pollution. The study comprised a series of interviews and questionnaires of key role pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
11
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 35 publications
3
11
1
Order By: Relevance
“…Interviews showed that mud brick making is a family based microoperation mostly headed by women to support their livelihoods and provide shelter. This is contrary to findings from commonly reported brick kilns where the majority of miners are males (Aniyikaiye et al, 2021;Das, 2015). This may be due to the complexity and tedious nature of producing fired bricks compared with sun-baked mud bricks produced in studied sites.…”
Section: Mudbrick Operation In Studied Sitescontrasting
confidence: 89%
See 1 more Smart Citation
“…Interviews showed that mud brick making is a family based microoperation mostly headed by women to support their livelihoods and provide shelter. This is contrary to findings from commonly reported brick kilns where the majority of miners are males (Aniyikaiye et al, 2021;Das, 2015). This may be due to the complexity and tedious nature of producing fired bricks compared with sun-baked mud bricks produced in studied sites.…”
Section: Mudbrick Operation In Studied Sitescontrasting
confidence: 89%
“…Mudbrick making seems to be a full-time job as operating hours are from 08:00 to 16:00 hr. Similar working hours have been reported in South Africa (Aniyikaiye et al, 2021) and India (Das, 2015). Brickfields were located on lands along waterfronts and floodplains often associated with soils having high clay content and for easy access to water which is consistent with Aniyikaiye et al (2021).…”
Section: Mudbrick Operation In Studied Sitessupporting
confidence: 85%
“…Research into this should be encouraged, however, this needs investment by local authorities into engineered landfills or even consolidated dumpsites. Anaikaiye et al (2021) argue that the use of locally available materials such as clay from riverbeds and anthills, firewood from a nearby forest or waste products from agriculture makes the brick-making process cheap and contributes positively to the socio-economic status of brick moulders. However, the low-cost firing technique contributes to emissions that are detrimental to the health of the brick moulders and the environment.…”
Section: Literature Reviewmentioning
confidence: 99%
“…However, the low-cost firing technique contributes to emissions that are detrimental to the health of the brick moulders and the environment. The green method of brick production which entails recycling of industrial wastes would enhance the development of a sustainable environment (Anaikaiye et al, 2021). The gradual transition from traditional techniques of brick baking to an environmentally friendly technology is necessary.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation